2013
DOI: 10.1371/journal.pone.0067387
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of the Intergeniculate Leaflet Lead to a Reorganization in Circadian Regulation and a Reversal in Masking Responses to Photic Stimuli in the Nile Grass Rat

Abstract: Light influences the daily patterning of behavior by entraining circadian rhythms and through its acute effects on activity levels (masking). Mechanisms of entrainment are quite similar across species, but masking can be very different. Specifically, in diurnal species, light generally increases locomotor activity (positive masking), and in nocturnal ones, it generally suppresses it (negative masking). The intergeniculate leaflet (IGL), a subdivision of the lateral geniculate complex, receives direct retinal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 47 publications
6
57
1
Order By: Relevance
“…The effect of light intensity on alpha is likely to reflect masking, with light expanding the active period and darkness reducing it in a diurnal mammal. These results are similar to what we have seen previously in intact grass rats (Gall et al, 2013). …”
Section: Discussionsupporting
confidence: 93%
“…The effect of light intensity on alpha is likely to reflect masking, with light expanding the active period and darkness reducing it in a diurnal mammal. These results are similar to what we have seen previously in intact grass rats (Gall et al, 2013). …”
Section: Discussionsupporting
confidence: 93%
“…These 28 animals were the same used in a previous report, which describes the behavioral effects of IGL lesions that also extended beyond the IGL (see [6] for surgical and histological details). Female grass rats do not exhibit estrous cycles in the laboratory [17], and do not differ from males in masking responses to light [3].…”
Section: Methodsmentioning
confidence: 99%
“…We recently showed that light pulses result in a significant reduction in activity levels following IGL lesions in diurnal grass rats ( Arvicanthis niloticus ), whereas control grass rats exhibit a significant increase in activity levels [6]. Therefore, destroying the IGL in these diurnal animals alters their masking patterns to resemble those of nocturnal animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we recently provided evidence that the IGL and OPT are involved in the masking response to light in the diurnal grass rat (Gall et al, 2013;Gall et al, 2014). However, it is not yet known if the SCN or vSPVZ contributes to masking in diurnal species.…”
mentioning
confidence: 99%